Child labor in Bangladesh villages: incidence, correlates and implications - Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2019)
The paper aims to improve our understanding about the prevalence and determinants of child labor in rural Bangladesh. Data for this study were obtained from 1995 sample survey of 3,809 eligible children aged 5 to 14 years in 150 villages. Findings reveal that about 42.5% of the children were in the labor force Nearly half of the employed children were engaged in livestock raising, 22,2% in household activities, 2, 7% in agricultural products. Children in labor were both abused and exploited as about 31.4% of working children reported that they were verbally assaulted, 4.2~·~ beaten_ 8.4% mentally tortured and 8.4% forced to work for long hours. School enrollment appears to be negatively associated with child labor. The probability of child to be a labor increases if his/her father is illiterate, land poor, and himself is a labor. The multivariate analysis reveals that children who have never been to or dropped out from school are 2.84 times more likely to enter into the labor force (p <. 00 l) when age of children is controlled. \\'hen other factors such as parental years of schooling, household ownership of land, occupation of father are systematically added to the regression equation, the negative influence of school enrollment on child labor remains statistically significant (p<.OOl ). The paper concludes that expanding public school network in the rural areas and making them attractive to children will bring a significant reduction of child labor.